18F-Florbetaben Amyloid PET Imaging: A Chinese Study in Cognitive Normal Controls, Mild Cognitive Impairment, and Alzheimer’s Disease Patients - Chang, Yan; Li, Can; Yang, Hui; Wu, Yue; Xu, Baixuan; Zhang, Jinming; Wang, Ruimin (Frontiers in Neuroscience, 2020)
Objective: To evaluate amyloid-β deposition with 18F-Florbetaben (FBB) PET imaging against 11C-PIB PET in cognitive normal controls (NC), mild cognitive impairment (MCI) and Alzheimer’s disease patients. Methods: We recruited 45 subjects (15 in each group of NC, MCI and mild/moderate AD) who had undergone dynamic 18F-FBB amyloid PET imaging. For comparison study, 17 participants, including 6 NC, 5 MCI and 6 AD patients, were also performed 11C-PIB PET imaging on separate days. Standardized uptake value ratio (SUVR) were calculated using the cerebellum as reference region with regions of interest (ROIs) manually defined on co-registered CT. Quantitative analysis of mean cortical uptake was calculated using global SUVR. Results: 1 (7%) of the 15 NC participants, 9 (60%) of 15 MCI patients and 12 (80%) of 15 AD patients had amyloid-positive lesions on 18F-FBB PET images. In AD patients, global SUVR was significantly higher than those of MCI patients (1.73±0.62 vs. 1.55±0.11, P<0.001) and CN subjects (1.73±0.62 vs. 1.13±0.43, P<0.001). In comparison study, 1 NC participant, 5 MCI and 5 AD patients had amyloid-positive lesions on 11C-PIB PET images. There was a significant linear correlation (r2=0.81, P< 0.001) between 18F-FBB and PIB global SUVR values. Conclusion: Our study suggests that 18F-FBB is a useful tracer for the evaluation of amyloid-β deposition in vivo, and global SUVR of 18F-FBB PET might be a reliable tool in the diagnosis of AD.